59.7k views
2 votes
Match the numerical expressions to their simplest forms

Match the numerical expressions to their simplest forms-example-1
User Timday
by
5.8k points

2 Answers

5 votes

(a^6b^(12))^(1/3) ========>
a^2b^4

\frac{(a^5b^3)^(1/2) }{(ab)^{- (1)/(2) } } ======>
a^3b^2

((a^(5) )/( a^(-3) b^(-4) ) )^{ (1)/(4)} ========>
a^2b

( (a^3)/(ab^(-6) ) )^{ (1)/(2) } ========>
ab^3

User Afternoon
by
6.2k points
2 votes
The answers are the following:
(a^6b^12)^1/3 = a^2b^4
(a^5b^3)^1/2 / (ab)^-1/2 = a^3b^2
(a^5/a^-3b^-4)^1/4=a^2b
(a^3/ab^-6)^1/2 = ab^3
User Akaya
by
5.8k points